Controle de Acesso IoT Escalável e Ciente de Contexto Suportando Múltiplos Usuários - Castro, Tiago O.; Macedo, Daniel F.; Santos, Aldri (Anais do Workshop de Gerência e Operação de Redes e Serviços (WGRS), 2018)
Internet of Things (IoT) supports many users and services controlling heterogeneous devices, implementing context aware applications. Thus, new access control models must be created in order to support more responsive, scalable, secure and autonomous management. This paper presents an attribute-based access control model, which applies conflict resolution and access delegation in a multi-user environment. With scalability in mind, we propose the caching of access permissions, as well as a policy model in which the devices with enough computational power perform part of the processing. The proposed model was implemented as part of the ManIoT architecture and evaluated by experiment on a testbed to demonstrate its efficiency. Results show that our model accelerates the access management, supporting environments where multiple users and applications seek to access devices concurrently.